2020
DOI: 10.1002/uog.20289
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic soft markers for detection of rectosigmoid deep endometriosis

Abstract: Objectives The aim of this study was to evaluate the use of ultrasound (US) soft markers as a first‐line imaging tool to raise suspicion of rectosigmoid (RS) involvement in women suspected of having deep endometriosis. Methods We included in this prospective observational study all patients with clinical suspicion of deep endometriosis who underwent diagnostic transvaginal US evaluation at our unit from January 2016 to February 2017. Several US soft markers were evaluated for prediction of RS involvement (pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
0
11
0
2
Order By: Relevance
“…United States radiology practices have been slow to adopt this technique because it is not a traditional part of the pelvic anatomy which has been routinely assessed by sonography. The sliding sign has been shown to have high specificity for the detection of posterior compartment adhesions but also has been shown to increase the detection of rectal DIE 7,16 . Our study showed that implementation of the sliding sign during routine protocol imaging for patients with appropriate clinical indications leads to an increase in the detection of posterior compartment DIE.…”
Section: Discussionmentioning
confidence: 57%
“…United States radiology practices have been slow to adopt this technique because it is not a traditional part of the pelvic anatomy which has been routinely assessed by sonography. The sliding sign has been shown to have high specificity for the detection of posterior compartment adhesions but also has been shown to increase the detection of rectal DIE 7,16 . Our study showed that implementation of the sliding sign during routine protocol imaging for patients with appropriate clinical indications leads to an increase in the detection of posterior compartment DIE.…”
Section: Discussionmentioning
confidence: 57%
“…Interpretation of this sign involves a steep learning curve and requires a minimum degree of training 82 , although the number of practice scans required to be considered competent may vary by trainee 83 . Ovarian immobility at the time of TVS is another important soft marker that has been associated with OE 84,85 , posterior-compartment DE 86 and ipsilateral SE [87][88][89] , as ipsilateral pelvic sidewall SE is less likely to be present in people with a mobile ovary (in the absence of DE or OE) 89 . Ovarian immobility to the pelvic sidewall is important to identify, using preoperative TVS, for patient counseling and surgical planning, as these women are at increased risk of requiring pelvic sidewall adhesiolysis and ureterolysis 90 .…”
Section: Ultrasoundmentioning
confidence: 99%
“…However, especially in patients with vaginal lesions, the combination of imaging techniques and clinical examination, including speculum examination and bimanual palpation, leads to a clearer view of the structures involved [21][22][23]. In addition, the dynamic examination includes not only imaging of endometriosis but also assessment of motility of the pelvic organs (sliding signs), tissue elasticity, and tenderness of affected organs (compartments) [6,24].…”
Section: Ultrasonography Does Not Allow the Definite Exclusion Of End...mentioning
confidence: 99%
“…Author contributions All the authors contributed to the study conception and design. The first draft of the manuscript was written by JK, , T [6,19], A [5,19,36], B [5,19,36], C [19,24,35,55], FA [39], and FU [19]. B Visualization of the other F compartments (except FA, FB, and FU) according to the #Enzian classification.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation